Perancangan Ulang Tata Letak Pedagang Pasar Panam Pekanbaru dengan Metode Association Rules-Market Basket Analysis - Yul, Faradila Ananda; Meirizha, St Nova; Denur, Denur; Dizha, Tazhi; Ardi, Hendri Ali (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study explains the redesign of the vendor layout at Panam Market in Pekanbaru using the association rules – market basket analysis method. The research aims to determine consumer shopping behavior patterns and to reorganize the vendor layout at Panam Market Pekanbaru. Based on the research results, it can be concluded that the reorganization of the vendor layout at Panam Market Pekanbaru was carried out based on the calculation of the support factor with a minimum value of 3% and the confidence value with a minimum of 60%. From the data processing results using the RapidMiner application, it was found that several vendor stalls in the market need to be positioned closer to each other based on the level of association, categorized as absolutely related, very important, fairly important, neutral, unimportant, and very unimportant.